The application of CRISPR/Cas9–based genome-wide screening to disease research - Xiuqin Chen; Min Zheng; Su Lin; Meiqing Huang; Shaoying Chen; Shilong Chen (Molecular and Cellular Probes, 2025)
High-throughput genetic screening serves as an indispensable approach for deciphering gene functions and the intricate relationships between phenotypes and genotypes. The CRISPR/Cas9 system, with its ability to precisely edit genomes on a large scale, has revolutionized the field by enabling the construction of comprehensive genomic libraries. This technology has become a cornerstone for genome-wide screenings in disease research. This review offers a comprehensive examination of how CRISPR/Cas9-based genetic screening has been leveraged to uncover genes that play a role in disease mechanisms, focusing on areas such as cancer development and viral replication processes. The insights presented in this review hold promise for the development of novel therapeutic strategies and precision medicine approaches.